Analyzing Recent Trends of Selected Commercial Fisheries of Namibia, 2000-2021 - Uahengo, Toivo; Msiska, Orton; Iikela, Sioni (European Journal of Applied Sciences, 2024)
Namibia has one of the world’s richest fisheries based on the Benguela upwelling system. This paper presents the selected principal stocks harvested for commercial purposes in the Namibian waters that are managed through the quota systems; drawing examples from comparable Eastern Boundary upwelling systems. It focuses on the selected marine fisheries of Merluccius capensis and Merluccius paradoxus (Hake), Lophius vomerinus (Monkfish), Trachurus capensis (Horse mackerel), Chaceon maritae (deep-sea Red crab), and Jasus lalandii Rock Lobster). Most of these fisheries need complementary management actions to be taken to improve their fishing catches, especially Lophius vomerinus and Trachurus capensis that are showing downward trends most probably due to overfishing. However, other indicators apportion the downward trend experienced between 2019 and 2020 was due to the outbreak of COVID-19 which reduced fishing trips. Hake, Deep-sea Red crabs, and Rock lobster are maintaining the recovery status quo. Hoplostethus atlanticus (Orange Roughy) and Sardinops sagax (Pilchard) have been drastically depleted and are currently put under moratorium. Apart from emphasizing the impact of El Nino on the fishery, questions still remain to be investigated on the contributions of the EL Nino phenomenon versus fishing pressure as well as specific parameters in the Benguela upwelling system that elicit these changes. It was also observed that the onset of fish declines occur well, at least 2 years, before the impact of El Nino is felt on land.